2010
DOI: 10.1074/jbc.m110.111880
|View full text |Cite
|
Sign up to set email alerts
|

α-Conotoxin AuIB Isomers Exhibit Distinct Inhibitory Mechanisms and Differential Sensitivity to Stoichiometry of α3β4 Nicotinic Acetylcholine Receptors

Abstract: Non-native disulfide isomers of ␣-conotoxins are generally inactive although some unexpectedly demonstrate comparable or enhanced bioactivity. The actions of "globular" and "ribbon" isomers of ␣-conotoxin AuIB have been characterized on ␣3␤4 nicotinic acetylcholine receptors (nAChRs) heterologously expressed in Xenopus oocytes. Using two-electrode voltage clamp recording, we showed that the inhibitory efficacy of the ribbon isomer of AuIB is limited to ϳ50%. The maximal inhibition was stoichiometry-dependent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
88
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 44 publications
(58 reference statements)
6
88
1
Order By: Relevance
“…This study confirms prior reports that at least two ␣3␤4 nAChR populations may be formed and that their relative expression levels depend on the molar injection ratio of the subunit mRNAs (1:20 versus 20:1). The pharmacology observed in this study matches that reported in other recent publications (27,28) that used less-extreme injection ratios (1:9 versus 9:1 or 1:10 versus 10:1). The lack of further changes in observed pharmacology after adoption of more extreme subunit ratios indicates that, as for ␣4 and ␤2 subunits (2,40,41), relatively pure populations of two different ␣3␤4 subunit assemblies are produced at the injection ratios used in this study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This study confirms prior reports that at least two ␣3␤4 nAChR populations may be formed and that their relative expression levels depend on the molar injection ratio of the subunit mRNAs (1:20 versus 20:1). The pharmacology observed in this study matches that reported in other recent publications (27,28) that used less-extreme injection ratios (1:9 versus 9:1 or 1:10 versus 10:1). The lack of further changes in observed pharmacology after adoption of more extreme subunit ratios indicates that, as for ␣4 and ␤2 subunits (2,40,41), relatively pure populations of two different ␣3␤4 subunit assemblies are produced at the injection ratios used in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The very similar properties of nAChR arising from 1:1 or 1:20 ␣3:␤4 mRNA injection ratios indicate that the same subunit assembly pattern predominates in both cases. This confirms previous reports that Xenopus oocytes injected with 1:1 and 1:9 ␣3:␤4 mRNA ratios express similar ␣3␤4 nAChR populations, whereas high ␣3:␤4 mRNA injection ratios result in expression of a distinctly different ␣3␤4 nAChR isoform (27,28). However, none of the outcomes observed from oocytes injected with any ratio of ␣3:␤4 mRNAs closely resembled the results obtained from the concatemeric ; n ϭ 4) (B), nicotine (10 Ϫ6.5 to 10 Ϫ3.5 ; n ϭ 4) (C), or the nAChR antagonist mecamylamine (10 Ϫ7.5 to 10…”
Section: ϫ3supporting
confidence: 80%
See 1 more Smart Citation
“…Mutational analyses provide evidence for PAM binding sites in the ECD at noncanonical interfaces analogous to dFBr Site III in a3b2 nAChRs at the b2/a3 interface (Seo et al, 2009) and in a4b2 nAChRs at the a4/a4 interface, which is also an ACh binding site (Mazzaferro et al, 2014;Olsen et al, 2014). Mutational analyses and computational docking also provide evidence for negative allosteric modulator binding sites equivalent to dFBr Site I at the canonical interfaces in a4b2 and a3b4 nAChRs (Grishin et al, 2010;Henderson et al, 2012). Based on our results, [ 3 H]dFBr should serve as an appropriate photoreactive PAM to identify its binding sites in a4b2 nAChRs and to identify other allosteric modulators that competitively inhibit photolabeling.…”
mentioning
confidence: 96%
“…It is noteworthy that non-native disulfide bond isomers of conopeptides can also provide useful membrane protein probes, further expanding on the pharmacology of conopeptides. For example, the two isomers of ␣-AuIB differ in their inhibitory mechanisms, with the AuIB (ribbon) form competitively inhibiting only ␣3␤4 nAChRs containing an ␣3 subunit in the fifth position, an effect distinct from the native AuIB (globular) form, which inhibited ␣3␤4 nAChRs independent of the fifth subunit, primarily through a noncompetitive mechanism (Grishin et al, 2010). Furthermore, a structural isomer of -TIA named NMB-1 was found to preferentially inhibit the sustained component of mechanically evoked current in DRG neurons, providing a novel diagnostic tool for the molecular definition of channels involved in hearing and pressureevoked pain (Drew et al, 2007).…”
Section: Discussionmentioning
confidence: 99%